NLS-72, national longitudinal study of the high school class of 1972 - National Center for Education Statistics ([Washington, DC] : National Center for Education Statistics, Office of Educational Research and Improvement, U.S. Dept. of Education : [For sale by the U.S. G.P.O., Supt. of Docs., 1994)
Contains all available data from the 1972 study of educational, vocational, and social aspirations of 19,001 high school seniors, including the four follow-up surveys and the 1984 postsecondary education transcript study.
Title from disk label.
Shipping list no.: 94-0014-E.
ISO 9660 format.
System requirements: DOS computer system capable of using a CD-ROM drive; CD-ROM drive.
Disk characteristics: CD-ROM.
Written in ASCII format.
Keywords: High school graduates -- United States -- Longitudinal studies -- Databases; High school graduates -- United States -- Statistics -- Databases